Suzaku Observations of the Cold Front in A3667: A Nonequilibrium Ionization State of the Intracluster Medium - Mona Shishido; Yuusuke Uchida; Takayoshi Kohmura (The Astrophysical Journal)
We present a systematic study of the thermodynamic properties of the intracluster medium (ICM), including the plasma conditions in the ICM, in the merging galaxy cluster A3667 using Suzaku. We analyze the X-ray spectra of the ICM between the northwestern and the southeastern radio relics across a prominent cold front in A3667 to search for the ICM in a nonequilibrium ionization (NEI) state. We find that the ICM inside the cold front exhibits an NEI state with an ionization parameter of (2.2 ± 0.4) × 10 ^11 s cm ^−3 at the 90% confidence level, which is lower than that expected from a collisional ionization equilibrium state of the ICM (i.e., n _e t > 10 ^12 s cm ^−3 ). The timescale calculated from the ionization parameter of the ICM inside the cold front is ${3.9}_{-0.8}^{+0.7}\,Myr$ , which is much shorter than the thermal equilibration timescale. A weak transonic sloshing motion might explain the possibility that the ICM inside the cold front of A3667 is in the NEI state. In addition, the NEI state of the ICM in A3667 seems to be associated with the elongated radio halo bridging the region between the northwestern radio relic and the prominent cold front in A3667 across the cluster center.